Spatio-ecological complexity measures in GRASS GIS - Rocchini, D.; Petras, V.; Petrasova, A.; Chemin, Yann H.; Ricotta, C.; Frigeri, A.; Landa, M.; Marcantonio, M.; Bastin, L.; Metz, M.; Delucchi, L.; Neteler, M. (Elsevier, 2017)
Good estimates of ecosystem complexity are essential for a number of ecological tasks: from biodiversity estimation, to forest structure variable retrieval, to feature extraction by edge detection and generation of multifractal surface as neutral models for e.g. feature change assessment. Hence, measuring ecological complexity over space becomes crucial in macroecology and geography. Many geospatial tools have been advocated in spatial ecology to estimate ecosystem complexity and its changes over space and time. Among these tools, free and open source options especially offer opportunities to guarantee the robustness of algorithms and reproducibility. In this paper we will summarize the most straightforward measures of spatial complexity available in the Free and Open Source Software GRASS GIS, relating them to key ecological patterns and processes.